Synthesis and Evaluation of Molecularly Imprinted Polymer for the Determination of the Phthalate Esters in the Bottled Beverages by HPLC - Ya-Feng Jin; Yi-Jun Zhang; Yu-Ping Zhang; Jun Chen; Xiao-Mao Zhou; Lian-Yang Bai (Journal of Chemistry)
A molecularly imprinted polymer (MIP) was prepared in acetonitrile by bulk polymerization, using di-n-octylphthalate (DOP) as a template molecular, α-methacrylic acid (MAA) as a functional monomer, and ethylene dimethacrylate (EDMA) as a crosslinker. Characterization and evaluation of the prepared MIP were carried out by scanning electron microscope (SEM), infrared absorption spectroscopy (IR), and the Scatchard analysis, respectively. Through the optimization of washing solvent, eluting solvent amount, flow rate of loading solution, and loading sample volume, an analysis method was established for DOP related compounds with high selectivity and sensitivity by using the selective molecularly imprinted solid-phase extraction (MI-SPE) technique. Moreover, under the optimal conditions, the extraction effects were comparatively investigated by using MIP cartridge, NIP cartridge, and the commercial PLS cartridge used especially for phthalic acid esters (PAEs), respectively. The results showed that the recoveries of spiked PAEs are in the range of 90.4%–97.8% with the relative standard deviation (RSD) of 1.6%–3.8% on the resulted MIP cartridge, whilst lower recoveries were obtained ranging from 80.2% to 88.9% with an RSD of 1.4%–5.2% on the commercial PLS cartridge.